The in Vitro Antimicrobial Efficacy of Propolis against Four Oral Pathogens: A Review - Nadine Michèle Waldner-Tomic; Rosmarie Vanni; Georgios N. Belibasakis; Thomas Thurnheer; Thomas Attin; Patrick R. Schmidlin (MDPI AG, 2014)
This study screened the available evidence for the in vitro antimicrobial efficacy of propolis, a natural herbal resin bee product, against a selection of three bacterial species of relevance to oral diseases. For this purpose, papers dealing with laboratory studies assessing minimum inhibitory concentration (MIC), minimum bactericidal concentrations (MBC) or the agar diffusion method to analyze the antimicrobial properties of propolis on three oral pathogens (S. mutans, P. gingivalis, F. nucleatum) and a yeast (C. albicans) are reviewed. Overall, a positive antimicrobial effect could be shown. However, when compared to the commonly used control substances (e.g., specific antibiotics, antiseptics and antifungals), propolis appeared less effective, depending on the bacterial strain, and required higher concentrations than the control substances, in order to show a measurable effect. Nevertheless, propolis as a natural herbal resin bee product can be considered as a natural antiseptic agent within the range of other herbal products, like sanguinarine. Therefore, it may be a valuable compound of non-synthetic, natural origin for patients seeking complementary agents and alternatives for "hard" chemicals.